(untitled) (Applied Biological Research, 2015)
The present paper reports the effect of nitrogen and sulphur application on their ratio, seed yield and protein related parameters in soybean. A random block design experiment with four treatments [control, nitrogen (urea @ 31.25 kg N ha-1) and sulphur (gypsum @ 20 kg S ha-1) alone or in combination] was conducted at PAU, Ludhiana (India) during kharif season 2012 using soybean cultivar ‘SL 525’ as a test crop. Nitrogen and sulphur alone or in combination significantly increased seed yield and decreased N:S ratio in the developing soybean leaves, seeds, roots and stem. Total soluble proteins, free amino acids and S-containing amino acids (only in leaves) in developing leaves and seeds increased due to nitrogen and sulphur supply. Results suggested that nitrogen alone causes maximum protein accumulation and sulphur alone or in combination with nitrogen maximally increases free amino acids, S-containing amino acids, seed yield and decreases N:S ratio in soybean.